2021
DOI: 10.1007/s11042-021-11289-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and evaluating beat gestures for social robots

Abstract: Natural gestures are a desirable feature for a humanoid robot, as they are presumed to elicit a more comfortable interaction in people. With this aim in mind, we present in this paper a system to develop a natural talking gesture generation behavior. A Generative Adversarial Network (GAN) produces novel beat gestures from the data captured from recordings of human talking. The data is obtained without the need for any kind of wearable, as a motion capture system properly estimates the position of the limbs/joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Participants were asked to sit in front of the robot (as shown in Figure 16 ). Immediately after, Qhali began a routine that consisted of gestures and phrases crafted from HRI literature [ 31 , 33 , 45 , 46 ], with collaboration from an experienced entertainer professional. The routine started with Qhali’s introduction and transitioned to the introduction of the therapist.…”
Section: Testing the Qhali Robot In A Controlled Environmentmentioning
confidence: 99%
“…Participants were asked to sit in front of the robot (as shown in Figure 16 ). Immediately after, Qhali began a routine that consisted of gestures and phrases crafted from HRI literature [ 31 , 33 , 45 , 46 ], with collaboration from an experienced entertainer professional. The routine started with Qhali’s introduction and transitioned to the introduction of the therapist.…”
Section: Testing the Qhali Robot In A Controlled Environmentmentioning
confidence: 99%
“…GANs aim to do implicit density estimation of the underlying distribution through the interplay of a generator that tries to produce samples that are representative of the data, and a discriminator that strengthens the generator by classifying samples as real (from the distribution) or fake (not from the distribution). Multiple gesture generation approaches added an adversarial objective as a term in a composite loss function, which increased the range of gesture motion although still deterministic for a given audio input [SB18, GBK*19, FNM20, YCL*20, ALNM20, RGP21, WLII21b, WLII21a, ZRMOL22, HES*22]. We discuss some notable examples below.…”
Section: Data‐driven Approachesmentioning
confidence: 99%
“…Current literature suggests that movements performed by robots are able to influence attitudes and perceptions toward them [ 2 , 6 , 7 ]. It has been found that robotic bodily expressions improve the understanding of affect (i.e., emotions and moods attributed to robots) [ 8 ], enhance the perception of trustworthiness [ 2 , 9 ], and awake empathetic responses toward robots [ 7 ]. Moreover, a combination of robotic speech and movements can increase feelings of familiarity [ 7 ] and foster human-like interaction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%